Screening of Variants in the Transcript Profile of Eutopic Endometrium from Infertile Women with Endometriosis during the Implantation Window - Da Broi, Michele Gomes; Plaça, Jessica Rodrigues; Silva, Wilson Araújo da, Jr; Ferriani, Rui Alberto; Navarro, Paula Andrea (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective Abnormalities in the eutopic endometrium of women with endometriosis may be related to disease-associated infertility. Although previous RNA-sequencing analysis did not show differential expression in endometrial transcripts of endometriosis patients, other molecular alterations could impact protein synthesis and endometrial receptivity. Our aim was to screen for functional mutations in the transcripts of eutopic endometria of infertile women with endometriosis and controls during the implantation window.Methods Data from RNA-Sequencing of endometrial biopsies collected during the implantation window from 17 patients (6 infertile women with endometriosis, 6 infertile controls, 5 fertile controls) were analyzed for variant discovery and identification of functional mutations. A targeted study of the alterations found was performed to understand the data into disease's context.Results None of the variants identified was common to other samples within the same group, and no mutation was repeated among patients with endometriosis, infertile and fertile controls. In the endometriosis group, nine predicted deleterious mutations were identified, but only one was previously associated to a clinical condition with no endometrial impact. When crossing the mutated genes with the descriptors endometriosis and/or endometrium, the gene CMKLR1 was associated either with inflammatory response in endometriosis or with endometrial processes for pregnancy establishment.Conclusion Despite no pattern of mutation having been found, we ponder the small sample size and the analysis on RNA-sequencing data. Considering the purpose of the study of screening and the importance of the CMKLR1 gene on endometrial modulation, it could be a candidate gene for powered further studies evaluating mutations in eutopic endometria from endometriosis patients.
Keywords: endometriosis; infertility; eutopic endometrium; RNA-sequencing; mutation